2017
DOI: 10.1016/j.clbc.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnetic Resonance Imaging in Detection of Pathologic Complete Remission in Breast Cancer Patients Treated With Neoadjuvant Chemotherapy: A Meta-analysis

Abstract: Pathologic complete remission after neoadjuvant chemotherapy has a role in guiding the management of breast cancer. The present meta-analysis examined the accuracy of contrast-enhanced magnetic resonance imaging (CE-MRI) and diffusion-weighted magnetic resonance imaging (DW-MRI) in detecting the response to neoadjuvant chemotherapy and compared CE-MRI with ultrasonography, mammography, and positron emission tomography/computed tomography (PET/CT). Medical subject heading terms and related keywords were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 82 publications
1
67
0
2
Order By: Relevance
“…This is probably due to the low accuracy that is still beyond an acceptable level in the clinic. In this study, we constructed a DL model by combining pre‐NAC and post‐NAC data and achieved an AUC of 0.98 and a PPV of 100%, which is much higher than previous studies for both traditional and functional MR imaging analysis . It shows great potential in clinical application for pCR prediction after NAC.…”
Section: Discussionmentioning
confidence: 88%
“…This is probably due to the low accuracy that is still beyond an acceptable level in the clinic. In this study, we constructed a DL model by combining pre‐NAC and post‐NAC data and achieved an AUC of 0.98 and a PPV of 100%, which is much higher than previous studies for both traditional and functional MR imaging analysis . It shows great potential in clinical application for pCR prediction after NAC.…”
Section: Discussionmentioning
confidence: 88%
“…Second, post-treatment DWI may provide a means to accurately assess extent of residual disease prior to surgery. A recent meta-analysis evaluating the utility of DWI for detecting pathologic complete response (pCR) after neoadjuvant chemotherapy reported a pooled sensitivity and specificity of 0.93 and 0.85, respectively, across eight studies with 539 total patients [47]. The performance of DWI for detecting pCR was not statistically different than for DCE-MRI, although their results suggested sensitivity to be higher by DWI and specificity to be higher by DCE-MRI and that a combination of both imaging techniques may enable more precise assessment of pathologic response to chemotherapy.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI), an important adjuvant tool for the detection and characterization of breast cancer, has also been utilized to monitor the effects of NAC, using dynamic contrast enhancement (DCE), as well as diffusion‐weighted imaging (DWI) and MR spectroscopy (MRS) . The MRI evaluation of therapeutic results during the course of NAC, performed in comparison to other methods and to histopathological findings, have shown potential for improving the early assessment and prediction of tumor response and for determining residual tumor size at the end of therapy before surgery . Several studies that compared response evaluation of DCE‐MRI to that of DWI and suggested that the combined use of these two methods has the potential to improve the diagnostic performance in monitoring NAC.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] The MRI evaluation of therapeutic results during the course of NAC, performed in comparison to other methods and to histopathological findings, have shown potential for improving the early assessment and prediction of tumor response and for determining residual tumor size at the end of therapy before surgery. [13][14][15][16] Several studies that compared response evaluation of DCE-MRI to that of DWI [17][18][19] and suggested that the combined use of these two methods has the potential to improve the diagnostic performance in monitoring NAC.…”
mentioning
confidence: 99%